2018
DOI: 10.1002/pbc.27458
|View full text |Cite
|
Sign up to set email alerts
|

A cost‐effectiveness analysis of Erwinia asparaginase therapy in children with acute lymphoblastic leukemia

Abstract: Objectives: Erwinia asparaginase is used as a second-line formulation after a neutralizing hypersensitivity reaction to the first-line formulation of asparaginase. Here, we have performed a costeffectiveness analysis of Erwinia asparaginase treatment. Methods: Children with acute lymphoblastic leukemia treated according to the Dutch ChildhoodOncology ALL-10 or ALL-11 protocol were included and initially treated with PEGasparaginase in the intensification phase. The total treatment costs of this treatment phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The pharmacoeconomic studies that indicate greater efficiency of the use of the non-pegylated form against Oncaspar V R , should now consider our results and include them in their analysis of the cost-effectiveness ratios of both forms of ASNase. 15,16 In conclusion, the activity of PEG-ASNase (Oncaspar V R ) remains stable for at least 14 days after reconstitution at temperatures of 4 C, À20 C and À80 C, which allows to reuse the leftover in posterior administration to the patient and consequently to save up to 50% in the treatment cost.…”
Section: Discussionmentioning
confidence: 95%
“…The pharmacoeconomic studies that indicate greater efficiency of the use of the non-pegylated form against Oncaspar V R , should now consider our results and include them in their analysis of the cost-effectiveness ratios of both forms of ASNase. 15,16 In conclusion, the activity of PEG-ASNase (Oncaspar V R ) remains stable for at least 14 days after reconstitution at temperatures of 4 C, À20 C and À80 C, which allows to reuse the leftover in posterior administration to the patient and consequently to save up to 50% in the treatment cost.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, accounting for these additional factors from a societal perspective would further favour the current versus the old treatment strategy, suggesting that our findings may be conservative. A recent study in The Netherlands on the cost-effectiveness of switching to Erwinia asparaginase versus discontinuing asparaginase following a hypersensitivity reaction to pegaspargase evaluated cost per life years saved using a wider perspective, including hospital costs, burden of switching and patient experience of the hypersensitivity reactions [51]. They found that although the cost was increased by switching to Erwinia asparaginase, the long-term clinical benefit and reduction in relapse resulting from this intervention versus discontinuing asparaginase completely merited their recommendation of the switch.…”
Section: Discussionmentioning
confidence: 99%
“…When Asp activity assays are not available, switching should always be considered at any grade of hypersensitivity, most commonly to Erwinase 29 , since even patients with CTCAE grade 1 allergy reactions have neutralizing antibodies causing undetectable activity levels 22 .…”
Section: Hypersensitivity and Therapeutic Drug Monitoringmentioning
confidence: 99%